O comportamento das ações das 10 maiores empresas listadas da carteira do IBOVESP: um estudo de evento sobre o início da pandemia do Covid-19 - Silva, Maria Jucilene Rodrigues Vieira da (2022)
At the beginning of the coronavirus outbreak, significant variations in world economic activity were observed, affecting stock exchanges around the world. In Brazil, there were also changes, with the shares of Brazilian companies listed on the B3 having performances that fluctuated. In order to contribute information to help identify and create administrative guidelines that can predict and minimize post-event impacts, this study analyzed the behavior of shares in the 10 (ten) largest Brazilian companies that make up the BOVESPA index (IBOVESPA) portfolio in the confirmation of the 1st case of Covid-19 in Brazil. The event study methodology was used to analyze whether there were normal or abnormal returns within a 5-day window before and after the event, the results confirmed the alternative hypothesis H1, that there was an abnormal return after the event was disclosed, where it was possible visualize the greatest negative impact on the date immediately following the D+1 announcement, as it is the first business day of the São Paulo stock exchange. However, after the effects of the event that impacted the market value of the Brazilian stock market on this date, a slow recovery was observed in the subsequent period, which followed the variation of the world market and directed the Brazilian government's protectionist government measures during the crisis brought about by the Covid19 pandemic. This study contributed to demonstrate that adverse events can affect the performance of a certain stock portfolio or a particular company, only in the short term, not portraying the market's operational reality, being subsequently absorbed by the market